Political determinants of budget deficit in Pakistan: An empirical investigation - Mumtaz Anwar; Munazza Ahmad (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
This study is an attempt to check some political factors determining budget deficit in Pakistan. It examines the short and long-run relationship between the Budget deficit, democracy and cabinet size for Pakistan's economy. The bounds testing approach to co-integration and (ECM) error-correction models, developed within an autoregressive distributed lag (ARDL) framework is applied to annual data for the period 1976 to 2009 in order to investigate whether a long-run equilibrium relationship exists between the budget deficit and these factors. The result of the bounds test indicates that there exist long-run relationship between the budget deficit and political variables. The results provide strong evidence that large government size will significantly add to the budget deficit. The democracy can help in reducing budget deficit but shows a weaker influence in case of Pakistan for the sample period.
Keywords: H62; K42; 330; Budget Deficit; Democracy; ARDL; Pakistan